The Pattern and Pace of Hyperacute Hemorrhage Expansion - Edlow, Brian L. (2012)
BACKGROUND: Intracerebral hemorrhage (ICH) expansion is common during the first 24 hours after onset, but the pattern and pace of hyperacute hemorrhage growth have not been described because serial imaging is typically performed over the course of hours and days, not minutes. The purpose of this study is to elucidate the spatial and temporal characteristics of hyperacute hemorrhage expansion within minutes of ICH onset. METHODS: An 86-year-old man with probable cerebral amyloid angiopathy developed an ICH while in the MRI scanner. Hyperacute hemorrhage growth was captured at three time points over a 14-minute interval of MRI data acquisition and at a fourth time point with CT 22 hours later. MRI and CT datasets were spatially coregistered, and three-dimensional models of ICH expansion were generated. RESULTS: Longitudinal analysis revealed that the spatial pattern of ICH growth was asymmetric at each time point. Maximal expansion occurred along the anterior-posterior plane during the first four minutes but along the superior-inferior plane during the next 10 minutes. The temporal pace of ICH expansion was also non-uniform, as growth along the anterior-posterior plane outpaced medial-lateral growth during the first 4 minutes (2.8 cm vs. 2.5 cm), but medial-lateral growth outpaced anterior-posterior growth over the next 10 minutes (1.0 cm vs. 0.2 cm). CONCLUSIONS: We provide evidence for asymmetric, non-uniform expansion of a hyperacute hemorrhage. These serial imaging observations suggest that hemorrhage expansion may be caused by local cascades of secondary vessel rupture as opposed to ongoing bleeding from a single ruptured vessel.